Chapter 5 Critical research on Black sporting experiences in the United States: Athletic activism and the appeal for social justice - Hawkins, Billy (Taylor & Francis, 2018)
Within the overlapping fields of the sociology of sport, physical education and health education, the use of critical theories and the critical research paradigm has grown in scope. Yet what social impact has this research had? This book considers the capacity of critical research and associated social theory to play an active role in challenging social injustices or at least in 'making a difference' within health and physical education (HPE) and sporting contexts. It also examines how the use of different social theories impacts sport policies, national curricula and health promotion activities, as well as the practices of HPE teaching and sport training and competition. Critical Research in Sport, Health and Physical Education is a valuable resource for academics and students working in the fields of research methods, sociology of sport, physical education and health.